RISING TIDE OF ALLERGIC DISEASES IN CHILDREN: CAUSES AND CONTEMPORARY APPROACHES (International journal of artificial intelligence, 2025)
Over recent decades, the prevalence of allergic diseases among children has escalated significantly worldwide. This phenomenon manifests in a broad spectrum of conditions including food allergies, allergic rhinitis, atopic dermatitis, and asthma. A complex interplay of genetic predisposition, environmental changes, altered microbial exposures, urbanisation, and lifestyle shifts contributes to this increase. For instance, climate change has extended pollen seasons and enhanced allergenicity, thereby raising risk for seasonal allergic rhinitis in children. Meanwhile, early-life risk factors such as Caesarean delivery, parental allergic disease, and indoor humidity have been identified in large meta-analyses. Modern preventive and therapeutic strategies are evolving. Allergen-specific immunotherapy (ASIT) in its subcutaneous and sublingual forms is being increasingly applied in paediatric populations. Biologics such as anti-IgE monoclonal antibodies show promise in treatment-resistant cases of chronic urticaria and severe food allergies. At the same time, early dietary introduction of allergenic foods, improved indoor air quality, microbial exposure, and barrier-preserving therapies are gaining attention for primary prevention and mitigation of disease severity. This paper aims to synthesise recent evidence on the causes behind the rising burden of paediatric allergic diseases, and to outline modern diagnostic, preventive and management approaches. After reviewing the literature, a research methodology is described which examined a cohort of children with allergic diseases in a tertiary care setting over a 12-month period. Results indicate that children exposed to higher ambient air-pollution levels and those with delayed dietary allergen introduction had more severe disease and reduced quality of life. In conclusion, the multifactorial nature of the problem necessitates a holistic and individualised approach, involving allergen avoidance, early life interventions, immunotherapy and emerging biologic therapies. The rising trend underscores an urgent need for public health initiatives, updated clinical guidelines and research into novel interventions.